IMPLEMENTATION OF ROOT CAUSE ANALYSIS ON PATIENT SAFETY IINCIDENCE IN HOSPITAL: LITERATURE REVIEW - Alifia, Redina Thara; Dhamanti, Inge (Journal of Public Health Research and Community Health Development, 2022)
ABSTRACT Background: Root cause analysis (RCA) is a process used by hospitals to reduce the level of patient safety incidents. The minimized application of root cause analysis has resulted in inevitable patient safety incidents. Research objectives: "‹"‹ This study aims to determine the application of RCA to patient safety incidents in hospitals. Method: The method used in this study was a literature review. Articles were obtained through the Pubmed, SAGE, and Google Scholar databases published in 2016-2021. Results: The implementation of RCA in 46 hospitals in France, the United States, and Hong Kong is known to run inadequately. This is due to the fact that the overall causative factors are not identified and the type of solution produced is ineffective in preventing the occurrence of the same patient safety incidents (PSI) in the future. Conclusion: The results of the article review shows that the application of RCA is not optimal. Therefore, it is necessary to improve the quality of RCA in hospitals. ABSTRAK Latar belakang: Analisis akar penyebab merupakan proses yang digunakan oleh rumah sakit untuk mengurangi tingkat kejadian insiden keselamatan pasien. Penerapan analisis akar penyebab yang belum maksimal menyebabkan insiden keselamatan pasien belum berhasil untuk dicegah.  Tujuan: Penelitian ini bertujuan mengetahui efektivitas dan hambatan penerapan RCA pada insiden keselamatan pasien di rumah sakit. Metode: Metode yang digunakan pada penelitian ini adalah scoping review. Pencarian artikel didapat melalui database Pubmed, SAGE, dan Google Scholar yang dipublikasikan pada tahun 2016-2021. Hasil: Penerapan RCA pada 46 rumah sakit di negara Prancis, Amerika Serikat, dan Hongkong diketahui belum berjalan secara optimal. Hal ini disebabkan, karena tidak mengidentifikasi faktor penyebab secara keseluruhan dan jenis solusi yang dihasilkan tidak efektif untuk mencegah terjadinya insiden keselamatan pasien (IKP) yang sama di masa mendatang. Kesimpulan: Hasil tinjauan artikel menunjukkan penerapan RCA belum optimal, sehingga dibutuhkan peningkatan kualitas RCA di rumah sakit.